The importance of monitoring cloud computing: An intensive review - Fahad, Ahmed Mohammed; Ahmed, Abdulghani Ali; M. N. M., Kahar (IEEE, 2017)
Recent advances in hardware and software of cloud computing are putting tremendous pressure on the administrators who manage these resources to provide uninterrupted services. Monitoring cloud computing plays a significant role in enhancing the quality of cloud computing services. Regular monitoring may help to adaptively scale resource utilization and determine service problems. It also helps to explore the usage patterns of different end users. System administrators should be familiar with cloud services monitoring and network tools. Previous studies considered different components of cloud computing such as properties, technology, privacy and security issues. This study reviews cloud monitoring tools that can help in monitoring and processing of data centers. In particular this study discusses the essential and desirable features of the existing cloud monitoring tools. Both open source and commercial tools were surveyed and their salient features were highlighted.